Prediction of Failure-Time for Soft Rock Tunnels based on Monitored Convergences. Issue 4 (May 2019) - Feng, Xianda; Jimenez, Rafael
Abstract: Predicting the failure-time for soft rock tunnels is an issue of great significance for disaster prevention and mitigation. The inverse-velocity (INV) method, which uses the rates of displacement to predict the failure-time, is often applied to predicting the failure-time of rock slopes. And the slope (SLO) method, which predicts the failure-time based on the slope (gradient), is another method for the same purpose. In this study, the validity of these two methods to predict failure-time of tunnels was evaluated by applying them to predicting the failure-time of the Ayas tunnel. The results show that the failure-time predicted by the INV method is closer to the actual failure-time compared with that predicted by the SLO method.